Boring Banks and Taxes - Rafael Aigner; Felix Bierbrauer (Center for Economic Studies and ifo Institute (CESifo), 2015)
How do taxes in the financial sector affect economic outcomes? We analyze a simple general equilibrium model with financial intermediation. We formalize a trade-off between tax policies that burden the owners of banks and tax policies that burden households. We also study the implications of the financial sector's exemption from value added taxation (VAT). Main results are that an increased taxation of the banks' profits goes together with a larger financial sector, as measured by the volume of loans and the employment in banking. We also show that the general presumption that the VAT-exemption is beneficial for banks is unjustified.
Keywords: G21; H21; H22; 330; taxation of the financial sector; financial activities tax; value added taxation